Targeted Gene Expression Profile Reveals CDK4 as Therapeutic Target for Selected Patients With Adrenocortical Carcinoma - Liang, Raimunde; Weigand, Isabel; Lippert, Juliane; Kircher, Stefan; Altieri, Barbara; Steinhauer, Sonja; Hantel, Constanze; Rost, Simone; Rosenwald, Andreas; Kroiss, Matthias; Fassnacht, Martin; Sbiera, Silviu; et al. (Frontiers in Endocrinology, 2020)
Adrenocortical carcinomas (ACC) are aggressive tumors with a heterogeneous prognosis and limited therapeutic options for advanced stages. This study aims to identify novel drug targets for a personalized treatment in ACC. RNA was isolated from 40 formalin-fixed paraffin-embedded ACC samples. We evaluated gene expression of 84 known cancer drug targets by reverse transcriptase quantitative real time-PCR and calculated fold change using 5 normal adrenal glands as reference (overexpression by fold change >2.0). The most promising candidate cyclin-dependent kinase 4 (CDK4) was investigated at protein level in 104 ACC samples and tested by in vitro experiments in two ACC cell lines (NCI-H295R and MUC1). The most frequently overexpressed genes were TOP2A (100% of cases, median fold change=16.5), IGF2 (95%, fold change=52.9), CDK1 (80%, fold change=6.7), CDK4 (62%, fold change=2.6), PLK4 (60%, fold change=2.8) and PLK1 (52%, fold change=2.3). CDK4 was chosen for functional validation, as it is actionable by approved CDK4/6-inhibitors (e.g. palbociclib). Nuclear immunostaining of CDK4 significantly correlated with mRNA expression (R=0.52, P<0.005). We exposed both NCI-H295R and MUC1 cell lines to palbociclib and found a concentration- and time-dependent reduction of cell viability, which was more pronounced in the NCI-H295R cells in line with higher CDK4 expression. Furthermore, we tested palbociclib in combination with insulin-like growth factor 1/insulin receptor inhibitor linsitinib showing an additive effect. In conclusion, we demonstrate that RNA profiling is useful to discover potential drug targets and that CDK4/6 inhibitors are promising candidates for treatment of selected patients with ACC.